2022
DOI: 10.1186/s13023-022-02362-1
|View full text |Cite|
|
Sign up to set email alerts
|

Birt-Hogg-Dubé syndrome encountered at rare lung disease clinic in Anhui province, China

Abstract: Background Diagnosis of rare diseases remains a challenge in China. We describe our experience with Birt-Hogg-Dubé syndrome (BHDS) encountered at a Rare Lung Disease Clinic recently established in China. Methods After the first patient with BHDS was recognized in 2017, a Rare Lung Disease Clinic with a multidisciplinary team of specialists was established. We retrospectively analyzed the data of consecutive patients with BHDS encountered from incep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…[1,3,5] In fact, many studies have shown that the prevalence of skin lesions in Asian BHD syndrome patients is less than half, even if skin lesions occur, it does not cause particular concern to patients or clinicians. [6,8,12] In this study, we did observe skin changes in the patient, which yet were histologically normal. Nevertheless, we still can not rule out the potential influence of the sampling sites on the final pathology results.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…[1,3,5] In fact, many studies have shown that the prevalence of skin lesions in Asian BHD syndrome patients is less than half, even if skin lesions occur, it does not cause particular concern to patients or clinicians. [6,8,12] In this study, we did observe skin changes in the patient, which yet were histologically normal. Nevertheless, we still can not rule out the potential influence of the sampling sites on the final pathology results.…”
Section: Discussionmentioning
confidence: 54%
“…Compared to skin lesions, pulmonary cysts are found to be more frequent in Asian BHD syndrome patients. [6,8,12] BHD syndrome-related pulmonary cysts are usually thin-walled, irregular-shaped and unevenly distributed in both lungs, especially in the lower lobe and near the mediastinum. [15] Pulmonary cysts may not cause noticeable respiratory symptoms until cysts rupture and pneumothorax happen at the advanced stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of the original article [ 1 ] would like to clarify that the official name and address for affiliation 1 is the following:…”
Section: Correction To: Orphanet Journal Of Rare Diseases (2022) 17:2...mentioning
confidence: 99%
“…In China, the average delay from first onset to final diagnosis is 10 years because of the high rate of misdiagnosis of the disease ( 2 ). Computed tomography (CT) is an important method for diagnosing BHD, and familiarity with the chest CT features of the syndrome can shorten the time to diagnosis ( 3 ). However, the mechanism of pulmonary cyst formation in BHD has yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%